Aortic calcification burden predicts deterioration of renal function after radical nephrectomy. Issue 1 (December 2017) - Fukushi, Ken; Hatakeyama, Shingo; Yamamoto, Hayato; Tobisawa, Yuki; Yoneyama, Tohru; Soma, Osamu; Matsumoto, Teppei; Hamano, Itsuto; Narita, Takuma; Imai, Atsushi; Yoneyama, Takahiro; Hashimoto, Yasuhiro; et al.
Abstract Background Radical nephrectomy for renal cell carcinoma (RCC) is a risk factor for the development of chronic kidney disease (CKD), and the possibility of postoperative deterioration of renal function must be considered before surgery. We investigated the contribution of the aortic calcification index (ACI) to the prediction of deterioration of renal function in patients undergoing radical nephrectomy. Methods Between January 1995 and December 2012, we performed 511 consecutive radical nephrectomies for patients with RCC. We retrospectively studied data from 109 patients who had regular postoperative follow-up of renal function for at least five years. The patients were divided into non-CKD and pre-CKD based on a preoperative estimated glomerular filtration rate (eGFR) of ≥60 mL/min/1.73 m2 or <60 mL/min/1.73 m2, respectively. The ACI was quantitatively measured by abdominal computed tomography before surgery. The patients in each group were stratified between low and high ACIs. Variables such as age, sex, comorbidities, and pre- and postoperative renal function were compared between patients with a low or high ACI in each group. Renal function deterioration-free interval rates were evaluated by Kaplan-Meier analysis. Factors independently associated with deterioration of renal function were determined using multivariate analysis. Results The median age, preoperative eGFR, and ACI in this cohort were 65 years, 68 mL/min/1.73 m2, and 8.3%, respectively. Higher ACI (≥8.3%) was significantly associated with eGFR decline in both non-CKD and pre-CKD groups. Renal function deterioration-free interval rates were significantly lower in the ACI-high than ACI-low strata in both of the non-CKD and pre-CKD groups. Multivariate analysis showed that higher ACI was an independent risk factor for deterioration of renal function at 5 years after radical nephrectomy. Conclusions Aortic calcification burden is a potential predictor of deterioration of renal function after radical nephrectomy. Trial registration This study was registered as a clinical trial:UMIN000023577